Contribuição para as metodologias de identificação e previsão da reação álcali-agregado (RAA) utilizando agregados graníticos e a técnica de microondas - Gomes Neto, David de Paiva (2014)
The alkali-aggregate reaction (AAR) is a pathological manifestation that occurs in concrete structures and has concerned engineers and users of construction for decades, throughout the world. Basically, it is a chemical reaction resulting from the interaction between alkalis released from cement and some silicates in the reactive aggregates. Aggregates have been studied and there are many disagreements as to the involvement of the granitic aggregates in the AAR. This study was originated from the absence of findings on the influence of compositional and microstructural characteristics of granite aggregates in the occurrence of AAR and the inadequacy of standardized testing methods for the prediction of reaction. This research presents contributions to the methods for prediction of the AAR using microwave treatment to accelerate the formation of reaction products. For this purpose, three granitic aggregates from Sergipe were used as reference for validation of the applicability of the technique. The selected experimental conditions have allowed rapid access to reactive mineral phases and formation of the reaction products. The results have showed that differences in reactive behavior of granitic aggregates are correlated to morphological aspects of quartz, as the presence of quartz subgrains and deformed quartz grains.